Penerapan Ice Breaking Pada Pembelajaran Hadist Dalam Meningkatkan Motivasi Belajar Santri TPQ-MDTA Baburrahman Lubuk Selasih Kabupaten Solok - Jara Karmila; Indah Muliati (CV. ITTC INDONESIA, 2026)
This research is motivated by the low learning motivation of students in hadist learning at TPQ-MDTA Baburrahman Lubuk Selasih, Solok Regency, which is caused by the physical and mental fatigue of students after participating in learning activities at formal schools from morning to evening. This research used a qualitative approach with a case study. This qualitative approach was chosen to explore the phenomenon holistically and contextually directly in the fiel. Data collection was conducted through field observations, in depth interviews with female teachers and students, and documentation, the results showed that four types of icebreakers were consistently applied: clapping (focused clapping, concentration clapping, and silence), physical dexterity movements and songs, and encouragement chants. Overall, the icebreaker technique proved effective as a strategic pedagogical instrument in enhancing no-foemal hadist learning.